The Influence of Human Resource Quality on Employee Performance with Competence as an Intervening Variable for Employees at RSU Mitra Sejati Medan - Sirait, Maria; Farida Ferine, Kiki; Robain, Wilchan (International Journal of Economics, Management and Accounting (IJEMA), 2024)
The quality of Human Resources (HR) contributes to employee performance, with employee competency being an important factor that acts as an intermediary or intervening variable in this relationship. When companies pay attention to and improve the quality of human resources through developing skills, knowledge and experience, this not only directly influences employee performance but also through increasing competency which facilitates employees in making a better contribution to overall organizational performance. This research aims to determine the effect of human resource quality on employee performance with competency as an intervening variable for employees at RSU Mitra Sejati Medan. This type of research is quantitative. The number of samples in this study was 82 respondents, the data analysis techniques used in this research were validity and reliability tests, classical assumption tests (normality, multicollinearity and heteroscedasticity) and hypothesis tests (path analysis techniques (t test and coefficient of determination) and sobel). The results of this research partially show that the quality of human resources has a positive and significant effect on competence with a t-count value (24.621 > 1.99045) and a significance value (0.00 < 0.05), the quality of human resources has a positive and significant effect on employee performance with a value of tcount (8.157 > 1.99045) and significance value (0.00 < 0.05), then competency has no effect on employee performance with a tcount value (0.588 > 1.99045) and significance value (0.558 > 0.05) and the quality of human resources has a positive effect on employee performance through competency at RSU Mitra Sejati Medan employees with a tcount value greater than ttable (4.93924 > 1.99045).